2003
DOI: 10.1002/aheh.200200508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Herbicide Metazachlor on Phytoplankton and Periphyton Communities in Outdoor Mesocosms

Abstract: The effects of the chloroacetanilide herbicide metazachlor have been investigated in outdoor artificial mesocosms. Decreasing phytoplankton densities were caused by the application, however, the communities recovered after 30 to 35 days. Periphyton growth was found to be affected not only by the herbicide application but by the presence of species with different ability to grow on artificial substrates. Zooplankton diversity was small due to low density of ingestible algae species. Oxygen saturation was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
3
7
1
Order By: Relevance
“…However, studies have explored the impact of metolachlor, metazachlor or acetochlor, chloroacetanilide herbicides which share a similar mode of action than alachlor (e.g. Noack et al, 2004;Relyea, 2009;Debenest et al, 2009;Roubeix et al, 2011aRoubeix et al, , 2012. For example, previous studies observed that metolachlor and metazachlor generated growth inhibition suggested by lower chlorophyll a levels of phototrophic biofilms exposed at 5 and 30 g L −1 (Noack et al, 2004;Debenest et al, 2009).…”
Section: Alachlor Toxicity Throughout Development Stagesmentioning
confidence: 99%
“…However, studies have explored the impact of metolachlor, metazachlor or acetochlor, chloroacetanilide herbicides which share a similar mode of action than alachlor (e.g. Noack et al, 2004;Relyea, 2009;Debenest et al, 2009;Roubeix et al, 2011aRoubeix et al, , 2012. For example, previous studies observed that metolachlor and metazachlor generated growth inhibition suggested by lower chlorophyll a levels of phototrophic biofilms exposed at 5 and 30 g L −1 (Noack et al, 2004;Debenest et al, 2009).…”
Section: Alachlor Toxicity Throughout Development Stagesmentioning
confidence: 99%
“…The experimental exposure of diatom communities to a chosen toxicant in enclosed controlled systems is then a suitable complementary approach. A large set of examples can be found in the literature with various herbicide molecules tested in either mesocosms or microcosms (Kosinski, 1984;Hamala and Kollig, 1985;Noack et al, 2003;Schmitt-Jansen and Altenburger, 2005;Mohr et al, 2008;Ricart et al, 2009;Vera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PS II inhibitors such as diuron and atrazine bind to 32 kilo daltons proteins in cyanobacterium Aphanocapsa 6308 and have kinetics similar to higher plants (Allen et al 1983). The exact site of action of pretilachlor in cyanobacteria is not clear; however, chloracetanilides (the class to which pretilachlor belongs) have been used in toxicity studies involving cyanobacteria (Noack et al 2003). In cyanobacteria Anabaena variabilis and Spirulina platensis, glyphosate acts by inhibiting the enzyme EPSPs, as is the case in higher plants (Powell et al 1992;Forlani and Campani 2002).…”
Section: Discussionmentioning
confidence: 98%